Directed Evolution of Pectin Methylesterases to Optimize Their Use in a Biofuels Application - Mankowitz, Rachel (My University, 2017)
One of the biggest challenges facing our society today is finding more effective ways to produce cleaner energy. With the uncertainty of crude oil prices, depletion of non-renewable energy resources, rising levels of greenhouse gas emissions, as well as political instability in producing countries, biofuels are a promising alternative (2). Biofuel is defined as fuel that is predominantly produced from biomass, which is simply organic matter (5). The key players in the production of biofuels are the enzymes produced by microbes that are capable of breaking down plant biomass into individual sugar monomers that can be fermented into biofuels such as ethanol.